Benign fibroosseous lesions - Cansu Köseoğlu Seçgin; Ömer Günhan; Ayşe Gülşahı (Acta Odontologica Turcica, 2016)
Benign fibroosseous lesions represent a group of lesions that share the same basic evolutive mechanism and are characterized by replacement of normal bone with a fibrous connective tissue that gradually undergoes mineralization. These lesions are presented by a variety of diseases including developmental, reactive-dysplastic processes and neoplasms. Depending on the nature and amount of calcified tissue, they can be observed as radiolucent, mixed or radiopaque. Their radiographic features could be well-defined or indistinguishable from the surrounding bone tissue. They can be asymptomatic as in osseous dysplasias and can be detected incidentally on radiographs, or they can lead to expansion in the affected bone as in ossifying fibroma. All fibroosseous lesions seen in the jaws and face are variations of the same histological pattern. Therefore, detailed clinical and radiographic evaluation in differential diagnosis is important. In this review, fibroosseous benign lesions are classified as osseous dysplasia, fibrous dysplasia and fibroosseous tumors; and radiographic features and differential diagnosis of these lesions are reviewed taking into account this classification.